Y2SiO5 environmental barrier coatings for niobium silicide based materials. (January 2015) - Lange, A.; Braun, R.; Mechnich, P.; Büttner, C. C.; Schulz, U.; Portebois, L.; Mathieu, S.; Vilasi, M.; Drawin, S.
Abstract : The oxidation behaviour of Nb silicide based alloys, considered as potential ultra-high temperature material for gas turbine engine applications, can be improved by chromia–silica forming coatings with M7 Si6 structure. To stabilise the protective oxide scales against water vapour corrosion in combustion atmospheres, environmental barrier coatings (EBCs) of yttrium silicate were deposited on an FeB modified M7 Si6 based bond coat using magnetron sputtering. The 15–20 μm thick ceramic top coats with an approximate chemical composition of 25Y–13Si–62O (at.-%) were dense and amorphous after deposition. They were annealed in vacuum to get a crystalline structure with the predominant phase Y2 SiO5 . Samples with this EBC system were tested in rapidly flowing water vapour at temperatures between 1100 and 1300°C for up to 16 h. At 1100 and 1200°C, significantly reduced mass gains were determined for samples with yttrium silicate top coat in comparison to those coated only with FeB containing layers. The EBC partially transformed into the Y2 Si2 O7 phase and exhibited microporosity. At 1300°C, the yttrium silicate layer decomposed forming yttrium oxides.